A 'planning revolution' or an 'attack on planning' in England: digitization, digitalization, and democratization. Issue 2 (3rd April 2022) - Boland, Philip; Durrant, Abigail; McHenry, Justin; McKay, Stephen; Wilson, Alexander
ABSTRACT: This article focuses on the planning–technology nexus. Recent work explores the potential of digital technology in overcoming the longstanding limitations of a lack of public engagement and citizen empowerment in the planning process. In August 2020, the Government published a White Paper to democratize, digitize, and digitalize the planning system. We interrogate whether these radical reforms constitute a 'planning revolution' or an 'attack on planning'; we focus on two important issues: democratic deficit and digital divide. The article examines how statements about digitization and digitalization may meet the Government's desire to make the planning process more inclusive (i.e. equitable, fair, just) by empowering greater numbers of people to influence planning decisions for their local communities. In this agenda-setting article, we reflect on the English planning landscape; more broadly, we critically reflect on the values and political rhetoric involved in embracing technological innovations, and how these intersect with societal concerns.